Answer:
![\huge \boxed{ \red{ \boxed{\begin{cases} \theta = {45}^( \circ) \\ \theta= {60}^( \circ) \end{cases} }}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/cmf1l5wuicl186mw1khq0pnjv5jke54d58.png)
Explanation:
to understand this
you need to know about:
let's solve:
distribute tan(θ):
=>tan²(θ)-(tan(θ)+√3tan(θ))+√3=0
remove parentheses:
=>tan²(θ)-tan(θ)-√3tan(θ)+√3=0
so this equation is now in standard form i.e ax²+bx+c=0
we can solve by factoring as we solve quadratic equation
factor out tanθ:
=>tan(θ)(tan(θ)-1)-√3tan(θ)+√3=0
factor out -√3:
=>tan(θ)(tan(θ)-1)-√3(tan(θ)-1)=0
group:
=>(tan(θ)-√3)(tan(θ)-1)=0
separate it as two different equation:
![\implies \begin{cases} \tan( \theta) - 1 = 0 \\ \tan( \theta) - √(3) = 0 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/ch3o9n6bjazn02pjf309yppogjhlw5xqmq.png)
add 1 and √3 to both sides to first and second equation respectively:
![\implies \begin{cases} \tan( \theta) - 1 + 1 = 0 + 1 \\ \tan( \theta) - √(3) + √(3) = 0 + √(3) \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/evx8j7fbqgvf8b1kg4qzfznp49wxbwk1xe.png)
![\implies \begin{cases} \tan( \theta) = 1 \\ \tan( \theta) = √(3) \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/4nag1cmi83q0sa7eo67ztu906bn7erjgj2.png)
![\therefore \begin{cases} \theta = {45}^( \circ) \\ \theta= {60}^( \circ) \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/j1f0yv3gef5hhu31hxzg2yr7cr8jwoibu1.png)